Some principles are more equal than others: Promotion‐ versus prevention‐focused effectuation principles and their disparate relationships with entrepreneurial orientation - Palmié, Maximilian; Huerzeler, Peter; Grichnik, Dietmar; Keupp, Marcus M.; Gassmann, Oliver (Strategic Entrepreneurship Journal, 2019)
Research Summary Recent research suggests that effectuation principles such as flexibility, precommitments, and affordable loss may differ substantially from one another. Responding to the call to clarify the effectuation concept, our study introduces the distinction between promotion‐ and prevention‐focused effectuation principles. It argues that promotion‐focused (prevention‐focused) principles are positively (negatively) associated with a firm's entrepreneurial orientation (EO). It further argues that causation is also promotion‐focused and positively associated with EO. An analysis of 151 Swiss energy small and medium‐sized enterprises supports this account. Thus, our study suggests that some effectuation principles are more similar to causation in their underlying regulatory focus and their relationship with EO than they are to other effectuation principles. We offer several paths for future research on effectuation, causation, and EO that emerge from these findings. Managerial Summary Practitioner‐oriented presentations and texts on entrepreneurial decision making frequently portray the means‐driven effectuation approach as opposite to the goals‐driven causation approach. Our study challenges this portrayal by highlighting substantial differences between the individual effectuation principles. Specifically, our research suggests that these principles differ in the underlying psychological processes and consequently in their relationships with key organizational attributes such as the firm's entrepreneurial orientation. In these important regards, some effectuation principles are actually more similar to causation than they are to other effectuation principles. Our study has substantial implications for the adoption of effectuation and for the “mixing and matching” of effectuation and causation. It not only makes a difference whether decision makers pursue an effectuation or causation approach, but also which effectuation principles they choose.